Atypical presentation of tight filum terminale with thoracic disc herniation: a case report - Taiju Miyagami; Hidetoshi Nojiri; Satoru Okada; Kiichi Mitsumoto; Kosuke Uemura; Toshio Naito (Journal of Medical Case Reports, 2024)
Abstract Background Tight filum terminale is a rare and challenging condition to diagnose because it presents with nonspecific symptoms and unclear imaging findings. This report documents an atypical case of tight filum terminale. Case presentation The patient was a previously healthy Asian 18-year-old male presenting with recurrent upper extremity and back pain, initially treated as nonspecific musculoskeletal pain. Notably, the patient’s symptoms were inconsistent with the dermatome, showing no correlation with his skin’s sensory innervation areas. In contrast to typical tight filum terminale presentations focused on lower extremity and lumbar region disturbances, this patient experienced pain and weakness predominantly in the upper extremities and back, hypothesized to result from traction myelopathy exacerbated by thoracic disc herniation. Investigations including blood and nerve function tests were inconclusive. However, a magnetic resonance imaging scan revealed a combination of tight filum terminale and tiny thoracic disc herniation. A diagnosis of tethered spinal cord syndrome was confirmed following further tests and imaging. The filum terminale was surgically removed, resolving the symptoms at a 7-month follow-up. Conclusions This case underlines the importance of including tight filum terminale as a differential diagnosis in cases of unexplained upper or lower extremity pain. Primary care practitioners, particularly those managing undefined symptoms, should consider tight filum terminale in their diagnostic approach.